Analisis Pengeluaran Pendidikan dan Pertumbuhan Ekonomi Di Indonesia (1970-2000) - Wahongan, Agus; Sepang, Alfriets (JBE (Journal of Business and Economics); Volume 2 No.1, 2003 JBE UNKLAB, 2003)
This paper introduces two models of analysis, those are simultaneous and error correction methods. Simultaneous method is used to estimate literacy rate, public expenditure on education and economic growth in three equationpostulates, while error correction model is used to estimate the long and short run equilibrin. The results of simultaneous estimation show school enrolment and national income have significant and positive influence on literacy rate. Public expenditure on education was significantly and positively influenced by public expenditure on health and literacy rate. Economic growth was determined by literacy rate and labour force as significant and positive. From the results of error correction estimations, all the models can be used as good estimators. The empirical study uses secondary data from many sources at 1970-2000 in logarithm natural.